2018
DOI: 10.1136/bcr-2018-225255
|View full text |Cite
|
Sign up to set email alerts
|

Meningovascular syphilis causing recurrent stroke and diagnostic difficulties: a scourge from the past

Abstract: We describe a case of a 49-year-old man who presented with recurrent strokes in the left middle cerebral artery territory, manifesting with dysphasia, higher cognitive deficits, motor deficits and subsequent infarcts in the right middle cerebral and anterior cerebral artery territories, manifesting with seizures, behavioural and social issues. A key issue of the case was the diagnostic difficulty faced by the physicians. 'Meningovascular syphilis' was subsequently confirmed and appropriate treatment was given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Most cases of meningovascular syphilis present with stroke (8) and many specialists use antiplatelet regimens (3,7). However, there are no recommendations (7,(14)(15)(16)(17). Intracerebral hemorrhage in neurosyphilis is rarely reported (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of meningovascular syphilis present with stroke (8) and many specialists use antiplatelet regimens (3,7). However, there are no recommendations (7,(14)(15)(16)(17). Intracerebral hemorrhage in neurosyphilis is rarely reported (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Meningovascular syphilis can be seen after 1 month; however, it is more often encountered in the late stage. 7 Late neurologic manifestations typically occur more than 5 years after infection (tertiary syphilis). Tabes dorsalis affects the dorsal spinal cord tracts and dorsal root ganglion and is characterized by radicular or severe, lancinating abdominal pain along with sensory gait ataxia and bladder dysfunction.…”
Section: Key Pointsmentioning
confidence: 99%
“…25 Although syphilis testing in cases of acute stroke may not be practical for every patient population, red flags that should raise the suspicion for meningovascular syphilis include stroke with concomitant or preceding symptoms of meningitis or encephalitis; stroke in young, sexually active individuals, especially in the absence of traditional cerebrovascular risk factors 32 ; and recurrent, unexplained strokes. 33 Obtaining a detailed social history, including sexual history, to uncover potential epidemiologic exposures is critically important and should not be shied away from by neurologists.…”
Section: Early Neurosyphilismentioning
confidence: 99%
“…In a study from Thailand, also with a reported high local prevalence of syphilis, 2.5% of 284 patients presenting with an acute stroke were diagnosed with neurosyphilis based on serum and CSF testing; among people younger than 50 years of age presenting with stroke, 4.4% met the definition for having neurosyphilis 25 . Although syphilis testing in cases of acute stroke may not be practical for every patient population, red flags that should raise the suspicion for meningovascular syphilis include stroke with concomitant or preceding symptoms of meningitis or encephalitis; stroke in young, sexually active individuals, especially in the absence of traditional cerebrovascular risk factors 32 ; and recurrent, unexplained strokes 33 . Obtaining a detailed social history, including sexual history, to uncover potential epidemiologic exposures is critically important and should not be shied away from by neurologists.…”
Section: Clinical Presentationmentioning
confidence: 99%